2018
DOI: 10.3892/etm.2018.5775
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation responses in patients with pulmonary tuberculosis in an intensive care unit

Abstract: Pulmonary tuberculosis caused by Mycobacterium tuberculosis remains a global problem. Inflammatory responses are the primary characteristics of patients with pulmonary tuberculosis in intensive care units (ICU). The aim of the present study was to investigate the clinical importance of inflammatory cells and factors for patients with pulmonary tuberculosis in ICU. A total of 124 patients with pulmonary tuberculosis in ICU were recruited for the present study. The inflammatory responses in patients with pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 37 publications
0
25
0
2
Order By: Relevance
“…In contrast, during tuberculous pleurisy, there is no significant increase in MC´s when compared to individuals with nonspecific pleuritis ( 77 ). When studying more severe pulmonary TB among patients admitted to the intensive care units, it was observed that these patients have an increased MCs in lung tissue ( 78 ). In fact, a recent study analyzed fibrotic tissue from post-mortem lung tissue microarrays from individuals with pulmonary TB and healthy control subjects ( 79 ).…”
Section: Mcs and Tuberculosismentioning
confidence: 99%
“…In contrast, during tuberculous pleurisy, there is no significant increase in MC´s when compared to individuals with nonspecific pleuritis ( 77 ). When studying more severe pulmonary TB among patients admitted to the intensive care units, it was observed that these patients have an increased MCs in lung tissue ( 78 ). In fact, a recent study analyzed fibrotic tissue from post-mortem lung tissue microarrays from individuals with pulmonary TB and healthy control subjects ( 79 ).…”
Section: Mcs and Tuberculosismentioning
confidence: 99%
“…Despite functions that overlap with •NO and CO, and its involvement in pathophysiological processes, the role of host-generated H 2 S in bacterial pathogenesis has been largely overlooked. Inflammatory responses ( Zumla et al., 2015 ; Liu Q.Y. et al., 2018 ) and metabolic reprogramming of innate and adaptive immune cells are associated with the progression of pulmonary TB ( Shi et al., 2016 ; Kumar et al., 2019 ).…”
Section: Role Of Host H 2 S In Tuberculosismentioning
confidence: 99%
“…Curcumin also inhibits NF-κB, a protein complex that controls target cell survival, cytokine production and transcription of DNA. Moreover, NF-κB is important in inducing the inflammatory response of the host's immune system causing inflammation and tissue damage [132]; inhibiting NF-κB can decrease DNA replication and proliferation of M. tuberculosis as well as decrease inflammation and tissue damage of the host cell. Fellutamide B, a proteasome inhibitor, may be used as adjunct treatment for tuberculosis.…”
Section: Discussionmentioning
confidence: 99%